2017
DOI: 10.1002/slct.201701755
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Control of Electrocatalytic Amorphous Nickel Phosphide to Increase Hydrogen Evolution Reaction Activity and Stability in Acidic Medium

Abstract: This work describes the electrocatalysis of amorphous nickel phosphide (Ni‐P) electrodeposited onto copper metal foil, for its use as a non‐noble metal catalyst for the hydrogen evolution reaction (HER) in 0.5 M H2SO4. Although electrodeposition offers many advantages over conventional high temperature and high pressure fabrication techniques, there are very few reports on the preparation of Ni‐P electrocatalysts via electrodeposition. This Ni‐P electrocatalyst exhibits good activity in acidic medium, with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The high-resolution spectrum of P 2p is divided into two types of phosphide species of oxidized and elemental P. The reason that oxidized P was observed is the surface passivation. 50,51 The P 2p spectral peaks from Cu−Co−P appear at 133.9 eV and 130 eV and are negatively shifted by −0.2 eV relative to the known position of elemental P (130.2 eV). 52 To confirm the change of chemical state of Cu−Co−P 20 after the durability test, we measured the XPS in Figure S12.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-resolution spectrum of P 2p is divided into two types of phosphide species of oxidized and elemental P. The reason that oxidized P was observed is the surface passivation. 50,51 The P 2p spectral peaks from Cu−Co−P appear at 133.9 eV and 130 eV and are negatively shifted by −0.2 eV relative to the known position of elemental P (130.2 eV). 52 To confirm the change of chemical state of Cu−Co−P 20 after the durability test, we measured the XPS in Figure S12.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Co 2p 3/2 in both Cu–Co and Cu–Co–P 20 was observed as metallic Co (Co 0 (778.25 eV) and Co δ+ (778.55 eV)) and oxidized Co 2+ /Co 3+ (781.9 eV/779.7 eV and 782.4 eV/780.3 eV) with satellite (786.7 eV and 787.2 eV). The oxidized metals are common when the TMPs are exposed to air condition . When comparing Cu–Co and Cu–Co–P 20 , binding energy shift of Cu and Co was observed in the positive direction.…”
Section: Resultsmentioning
confidence: 99%
“…As-prepared nickel/nickel phosphide/carbon cloth electrodes exhibit a cathodic current of 10 mA/cm 2 at the overpotential of 164 mV in a 0.5 M H 2 SO 4 solution and a Tafel slope of 76 mV/dec. Wasalathanthri et al prepared amorphous nickel phosphide thin films on Cu foil by electrodeposition at a constant current density of 10 mA/cm 2 for 10 min, which exhibits a good activity and long-term stability in acidic medium, with a potential of −222 mV to achieve 10 mA/cm 2 [140]. Wang et al reported the preparation of amorphous sponge-like nickel phosphide-carbon nanotube (Ni x P/CNT) hybrid electrodes through CV deposition [143].…”
Section: Electrochemical Depositionmentioning
confidence: 99%
“…Enhancing energy conversion and storage systems, such as water electrolysis, fuel cells, and metal–air batteries, are needed for clean and efficient alternate energy sources and to reduce pollution that is harmful to human health . These systems involve either hydrogen evolution reaction (HER) or oxygen reduction reaction (ORR) at the cathode, and oxygen evolution reaction (OER) or oxidation of fuels at the anode .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of transition metal chalcognides and phosphides ,,, exhibit high HER activity. Owing to their higher affinity toward H 2 , transition metal phosphides (TMPs) are also excellent catalysts in other processes, such as hydrodesulfurization, hydrodenitrification, and CO hydrogenation, indicating a vast applicability of TMP HER catalysts .…”
Section: Introductionmentioning
confidence: 99%